Sterol transfer by atypical cholesterol-binding NPC2 proteins in coral-algal symbiosis - Hambleton, Elizabeth A.; Jones, Victor; Mägele, Ira; Sachsenheimer, Timo; Guse, Annika (eLife, 2019)
Diversification of a conserved cholesterol binder drives functional replacement of cholesterol with symbiont-produced sterols in corals living in nutrient-poor environments.